The Effect of Leadership and Competence on Organizational Citizenship Behavior (OCB) Mediated by Job Satisfacti - Ningrum , Widya; Liana, Lie (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the effect of leadership and competence on Organizational Citizenship Behavior (OCB), mediated by job satisfaction. This research employs a quantitative approach with a population consisting of 58 employees of BPPKAD, Wonosobo Regency. The data were processed using SPSS version 26. The data analysis techniques include respondent description, variable description, validity test, reliability test, F-test, coefficient of determination (R²), t-test, and Sobel test. The results of the study indicate that leadership has a positive effect on job satisfaction, competence has a positive effect on job satisfaction, leadership has a positive effect on OCB, competence has a positive effect on OCB, and job satisfaction has a positive effect on OCB. However, job satisfaction does not mediate the effect of leadership on OCB, while job satisfaction mediates the effect of competence on OCB.